2009
DOI: 10.7182/prtr.19.2.g226182714730n07
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in caregivers providing care for lung transplant candidates

Abstract: Caregivers reported favorable levels of quality of life, physical health, and mood during the pretransplant waiting phase. However, problem areas for caregivers during this time included fatigue, depression, and the financial impact of the transplant. Data analyses indicated that depression, caregiver general health, impact on finances, and lack of family support had the greatest effect on caregivers' quality of life. Nurses are urged to recognize the role of caregivers in the transplant process, ask about and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Studies have shown that caregivers providing care for family diagnosed with cancer often benefit from being employed (Kim et al, 2006;Lefaiver et al, 2009). Working while caring for family members may offer respite for caregivers, provide opportunities to refresh psychological resources and concentrate on something other than their responsibilities at home.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that caregivers providing care for family diagnosed with cancer often benefit from being employed (Kim et al, 2006;Lefaiver et al, 2009). Working while caring for family members may offer respite for caregivers, provide opportunities to refresh psychological resources and concentrate on something other than their responsibilities at home.…”
Section: Discussionmentioning
confidence: 99%
“…During the waiting period, relatives tend to forsake their own needs, activities and friends in their daily life (8,14,15) and they experience an increased caregiver burden (16,17). Studies have shown economic strain for more than half of the relatives of patients on the waiting list (18,19). Therefore, different types of support and information are a matter of great importance for the relatives (8,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Transplant patients and their relatives felt that they had experienced something unique at the same time, which might contribute to a positive connectedness (9). Therefore it is important that healthcare professionals understand that patients and relatives undergo the process together (19). Despite the importance of relatives, healthcare professionals, to a great extent focus only on the needs of the patient (23).…”
mentioning
confidence: 99%
“…Most relatives also report economic strain because of loss of income, extra costs of transportations and accommodation associated with medical visits during the period of care (Lefaiver et al, 2009, Rodrigue and Baz, 2007, Ulrich et al, 2004. While waiting, relatives tend to disregard their own needs, hobbies, and friends (Bohachick et al, 2001, Kurz, 2002, Meltzer and Rodrigue, 2001) and relatives experience an increased workload (Kurz, 2001, 4 McCurry and Thomas, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals must be aware that most patients do not undergo the process alone but also have relatives and therefore healthcare professionals must give these persons targeted information and support (Lefaiver et al, 2009). In the nursing process, Travelbee (1971) stated that it is important to pay attention to relatives, acknowledge their significant support and the importance of their presence.…”
Section: Introductionmentioning
confidence: 99%